Tworzenie sytuacji sprzyjających zaangażowanej współpracy dzieci w wieku wczesnoszkolnym - Goretta Siadak (Problemy Wczesnej Edukacji)
The aim of this article is to present the possibility of the organisation of situations conducive to cooperation between pupils of early school age. In various parts of the article the following will be discussed: teacher-tutoring, and peer-tutoring in the Polish education system. The project Academic Centre of Creativity will be presented. This project was carried out by the research team at the Department of Didactics and Studies in the Culture of Education, Kazimierz Wielki University. The main objective of the project was to develop (testing and popularisation) of an innovative work model for teachers/students with the student based on Lev Vygotsky’s Sociocultural Theory. The research was carried out among the students of the first stage of education in grades I–III five “school exercise” located in Kujawsko-Pomorskie. The main part of the project ACK was a teaching experiment, during which observations were made, the activity of individual students and their participation in activities (group) was analysed in four areas: language, mathematics, science, and art. Owing to the multi-stage project, in the article emphasis was put on the practical aspect of the experiment, which was the organisation of the classroom culture as a social learning environment. During this process two forms of peer interaction were initiated: learning in collaboration and peer-tutoring. We analysed: the preparation phase conditions stimulating cooperation, the stages of development of collaborative learning and peer-tutoring, the benefits of collaboration and peer-tutoring (same-age peer-tutoring, cross-age peer-tutoring) among students of early childhood education.